2008
DOI: 10.1016/j.jpainsymman.2007.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Patients Dying with Dementia: Experience at the End of Life and Impact of Hospice Care

Abstract: To evaluate the impact hospice enrollment has on the terminal care of patients with dementia and describe the symptom burden these patients experience, caregivers of dementia decedents were assessed in a mortality follow-back survey. Patients had been managed through academic outpatient geriatric clinics in Chicago, IL. A total of 135 family members or other knowledgeable informants of persons who had died with dementia were queried about the patient's preferred location of death, location of death, satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
129
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(135 citation statements)
references
References 33 publications
4
129
1
1
Order By: Relevance
“…283 (100) 15 (22) 18 (20) All 76 (66), [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] 35 (55), 44 (42), [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] 155 (55) …”
Section: (100)mentioning
confidence: 99%
“…283 (100) 15 (22) 18 (20) All 76 (66), [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] 35 (55), 44 (42), [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] 155 (55) …”
Section: (100)mentioning
confidence: 99%
“…In contrast, pain and shortness of breath are frequently reported in dementia patients. Studies (see Box 1 for the methods of the literature search [29][30][31][32]) report pain in 12% to 76% of patients [28,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. The lower percentages were reported in studies using the Minimum Data Set (MDS) [43], which is mandated in US nursing homes and is known for underreporting [48], in regards to "uncontrolled pain" [38] and in more recent work related to pain [44].…”
Section: Symptoms and Treatment At The End Of Lifementioning
confidence: 99%
“…Agitation is a symptom which is less frequently assessed in studies on the last phase of life, but may be as common as pain and shortness of breath [28,34,44,53,54]. One study found that psychiatric symptoms such as agitation and depression were less bothersome to family members than pain, breathing problems, and memory loss [46].…”
Section: Symptoms and Treatment At The End Of Lifementioning
confidence: 99%
See 2 more Smart Citations